A transient ischemic environment induces reversible compaction of chromatin. Issue 1 (December 2015) - Kirmes, Ina; Szczurek, Aleksander; Prakash, Kirti; Charapitsa, Iryna; Heiser, Christina; Musheev, Michael; Schock, Florian; Fornalczyk, Karolina; Ma, Dongyu; Birk, Udo; Cremer, Christoph; Reid, George
Abstract Background Cells detect and adapt to hypoxic and nutritional stress through immediate transcriptional, translational and metabolic responses. The environmental effects of ischemia on chromatin nanostructure were investigated using single molecule localization microscopy of DNA binding dyes and of acetylated histones, by the sensitivity of chromatin to digestion with DNAseI, and by fluorescence recovery after photobleaching (FRAP) of core and linker histones. Results Short-term oxygen and nutrient deprivation of the cardiomyocyte cell line HL-1 induces a previously undescribed chromatin architecture, consisting of large, chromatin-sparse voids interspersed between DNA-dense hollow helicoid structures 40–700 nm in dimension. The chromatin compaction is reversible, and upon restitution of normoxia and nutrients, chromatin transiently adopts a more open structure than in untreated cells. The compacted state of chromatin reduces transcription, while the open chromatin structure induced upon recovery provokes a transitory increase in transcription. Digestion of chromatin with DNAseI confirms that oxygen and nutrient deprivation induces compaction of chromatin. Chromatin compaction is associated with depletion of ATP and redistribution of the polyamine pool into the nucleus. FRAP demonstrates that core histones are not displaced from compacted chromatin; however, the mobility of linker histone H1 is considerably reduced, to an extent that far exceeds the difference in histone H1 mobility between heterochromatin and euchromatin. Conclusions These studies exemplify the dynamic capacity of chromatin architecture to physically respond to environmental conditions, directly link cellular energy status to chromatin compaction and provide insight into the effect ischemia has on the nuclear architecture of cells.